Effects of deoxynivalenol on mitochondrial dynamics and autophagy in pig spleen lymphocytes. (June 2020) - Ren, Zhihua; Guo, Chaoyue; He, Hongyi; Zuo, Zhicai; Hu, Yanchun; Yu, Shumin; Zhong, Zhijun; Liu, Haifeng; Zhu, Ling; Xu, Shengyu; Deng, Youtian; Hu, Hui; et al.
Abstract: Deoxynivalenol (DON) is a type of cytotoxic mycotoxin that targets the mitochondria in cells. However, effects of DON on mitochondrial dynamics have not yet been reported. In this study, we investigated the effects of DON on mitochondrial dynamics and mitochondrial autophagy. Spleen lymphocytes of primary pigs were treated with different concentrations of DON. 24 h later, the cells were collected and the indexes were measured as follow: contents of ROS and MDA; activities of SDH and SOD; total antioxidant capacity; expression of MFN1, MFN2 and OPA1; the mRNA expression of the genes encoding mitochondrial autophagy proteins LC3 and P62, as well as mitochondrial respiratory chain complex activities. The results showed that, compared with the control group, the contents of ROS and MDA in the DON groups increased, while the activities of T-AOC, SDH and SOD decreased in a dose-dependent manner. With increasing DON concentrations, the expression levels of MFN1/2, OPA1 and mitochondrial respiratory chain complex activities decreased, while LC3, P62 increased. We suspect that DON causes oxidative damage, which in turn leads to down-regulation of MFN1, MFN2, OPA1 and up-regulation of LC3 and P62 mRNA, thereby inhibiting mitochondrial fusion and promoting mitochondrial autophagy. Highlights: The toxicological study of DON was advances to the level of mitochondrial dynamics. It was found that the effect of DON on mitochondrial dynamics was dose-dependent. Providing new ideas or strategies for the development of DON antagonists.